2018
DOI: 10.1111/jac.12290
|View full text |Cite
|
Sign up to set email alerts
|

Yield potential and salt tolerance of quinoa on salt‐degraded soils of Pakistan

Abstract: Quinoa is recently introduced to Pakistan as a salt‐tolerant crop of high nutritional value. Open field trials were conducted to evaluate its performance on normal and salinity/sodicity‐degraded lands at two locations of different salinity/sodicity levels, S1 (UAF Farm, Normal Soil), S2 (Paroka Farm UAF, saline sodic), S3 (SSRI Farm, normal) and S4 (SSRI Farm, saline sodic) during 2013–2014. Two genotypes (Q‐2 and Q‐7) were grown in lines and were allowed to grow till maturity under RCBD split‐plot arrangement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 42 publications
5
45
1
Order By: Relevance
“…Among these, lipid peroxidation particularly is considered more drastic because of its free radicals propagation by chain reaction (Farmer and Mueller ). However, quinoa plants activate antioxidative system (SOD, POD, CAT, APX) to reduce these damages (Amjad et al , Iqbal et al ), which is also observed in the present study under salinity (Fig. and Table ).…”
Section: Discussionsupporting
confidence: 83%
“…Among these, lipid peroxidation particularly is considered more drastic because of its free radicals propagation by chain reaction (Farmer and Mueller ). However, quinoa plants activate antioxidative system (SOD, POD, CAT, APX) to reduce these damages (Amjad et al , Iqbal et al ), which is also observed in the present study under salinity (Fig. and Table ).…”
Section: Discussionsupporting
confidence: 83%
“…Leaf photosynthesis can be lowered by the reduction of stomatal conductance as a result of water imbalance under salt stress [25]. The rate of photosynthesis in salt-tolerant species generally has been least affected than that in salt-sensitive species [9]. Whereas, in the present study, both varieties exhibited a similar level of photosynthetic attributes indicating that the difference of resistance of Sahiwal-2002 and Sadaf may not be directly related to these attributes.…”
Section: Chlorophyll Contentscontrasting
confidence: 60%
“…The salt causes the wilting of the leaves even when the much moisture (or water content) is present and the leaves become dull and having gray leaf tips. The salinity causes also adverse effects in the form of physiological dysfunctions and a decrease in the yield of a crop [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Not all studies concern varieties grown in Chile, as quinoa has recently been introduced to Pakistan (eminently agricultural country and subjected to adverse weather conditions). For example, Iqbal et al (2019) have observed that most tolerant genotypes had higher SOD (superoxide dismutase), the antioxidant enzyme that lowers ROS levels, proline (an osmolyte), phenols (antioxidants), K + contents, and Na + content in the shoot as compared to more sensitive genotypes. High levels of antioxidants and K + /Na + of resistant genotype provide greater tolerance to saline stress and might offer higher yields in both normal and salt-affected soils.…”
Section: Xerohalophyte Speciesmentioning
confidence: 99%